Predictive Factors for Blood Stream Infections in Children with Cancer. (1st August 2013) - Doganis, Dimitrios; Asmar, Basim; Yankelevich, Maxim; Thomas, Ronald; Ravindranath, Yaddanapudi
Abstract : Blood Stream Infections (BSI) are among the most serious infections in children with cancer and are potentially life threatening. A retrospective study of blood cultures obtained from all newly diagnosed patients—from January 1, 2005 to December 31, 2009—with malignancy was conducted. In this study, our aim was to identify clinical and laboratory variables associated with a BSI in a child with malignancy. Among 1004 separate infection episodes detected in 261 patients, 198 were classified as true BSI (19.7%). Univariate analysis showed that factors such as younger age, race, temperature ≥40°C, presence of chills and hypotension, time interval from the last chemotherapy, treatment for recurrent disease or a history of Stem Cell Transplantation, low hemoglobin, low-Platelets count, and Absolute Neutrophils count less than 4 × 10 9 /L were predictive for a BSI. Patients with a catheter in place and especially if this catheter was tunneled and/or multiple lumen were more likely to have a BSI. Being on antibiotics, the history of a BSI during the previous month and having received a red cell or platelet transfusion during the prior 15 days also increased the likelihood for a BSI. According to a multivariate logistic regression analysis, the factors that remained significant were the younger age, the African American race, the presence of chills or hypotension, the use of tunneled or multiple lumen catheters, the administration of antibiotics during the previous 15 days and a low-PLT count.